Fossil fuel subsidies and GHG emissions: Firm-level empirical evidence from developing Asia - Dina Azhgaliyeva; Hai Le (Asian Development Bank Institute (ADBI), 2023)
Given the commitment of G7 and G20 countries to the gradual elimination of fossil fuel subsidies and their advocacy for other nations to follow suit, this study examines the effects of such subsidies on firms' GHG emissions. Utilizing a dataset comprising 3,359 firms across seven countries in developing Asia, namely, the People's Republic of China (PRC), India, Indonesia, Malaysia, Pakistan, Thailand, and Viet Nam, we demonstrate that a firm's GHG emissions, encompassing both absolute GHG emissions and GHG emission intensity, exhibit an upward trajectory concurrent with an escalation in fossil fuel subsidies. This observed correlation extends to both subsidies per unit of energy and subsidies relative to GDP, with subsidies allocated to crude oil exerting a notably more pronounced impact than those designated for gas and electricity. Furthermore, our analysis demonstrates heterogeneity in outcomes across firms situated in diverse regions and sectors. Particularly, the impact of fossil fuel subsidies on firms' emissions is greater in sectors characterized by low energy consumption, compared to those with high energy consumption. This discrepancy is probably attributed to a lack of cost-competitive low-carbon substitutes and non-energy emissions. While fossil fuel subsidies have a positive impact on firms' GHG emissions in Southeast Asia, no significant effect is documented for the PRC or South Asia.
Keywords: Q30; Q38; Q42; Q48; Q53; Q58; 330; fossil fuel subsidy; energy subsidy; GHG emissions; hard-to-abate sectors